Rasmussen's encephalitis: A rare case report - Sadhanandham Shrinuvasan; Ranganathan Chidambaram (Wolters Kluwer Medknow Publications, 2015)
Rasmussen's encephalitis (RE) is a chronic neurological disorder, characterised by unilateral inflammation of the cerebral cortex leading to progressive neurological and cognitive deterioration. Advances in neuroimaging suggest that progression of the inflammatory process seen with magnetic resonance imaging (MRI) might be a good biomarker in RE. We present here a case of 8-year-old male child presented with repeated episodes of drug resistant seizures leading to intellectual impairment and cognitive deterioration. Further MRI was done which shows diffuse left cerebral atrophy.